Amanat Agung dalam Bayang-bayang Disinformasi: Strategi Gereja Menghadirkan Kebenaran Injil di Era Post-Truth - Sumual, Elisa Nimbo; Arifianto, Yonatan Alex (Sekolah Tinggi Teologi Torsina Surakarta, 2025)
In the post-truth era, the abundance of conflicting news and hoaxes often overshadows objective truth, as personal opinions and subjective values predominate. Even relativity determines truth, leading to widespread disinformation in digital and social spaces. The Church, as the recipient of the Great Commission, currently faces challenges in communicating the Gospel in its pure form. This challenge is due to the presence of biased and manipulative information that distorts the truth. The inability of some Christians to distinguish between theological truth and false narratives has weakened the Church's witness. The purpose of this study is to formulate theological and practical strategies for the Church in communicating the Great Commission authentically amid the truth crisis. Using a descriptive qualitative method with a literature review approach, it can be concluded that an understanding of the essence of the Great Commission in theology, as well as knowledge of the post-truth crisis and the church's challenges in proclaiming the truth, are crucial. It is hoped that the results will not hinder the actualization of the Great Commission as a mandate to proclaim truth amid the post-truth crisis and that the church will develop strategies to address disinformation in its mission to proclaim truth in a world darkened by disinformation. Abstrak Banyaknya berita simpang siur dan hoak di era post-truth, kebenaran objektif sering kali tersingkir oleh opini dan nilai subjektif pribadi manusia. Bahkan adanya relativitas juga menentukan kebenaran sehingga menimbulkan disinformasi yang meluas dalam ruang digital dan sosial. Gereja sebagai penerima mandat dari Amanat Agung dewasa ini menghadapi problem dalam menyampaikan Injil secara murni. Sebab adanya informasi yang bias dan manipulatif terkait kebenaran yang dinarasikan. Ketidakmampuan sebagian umat Kristen dalam membedakan antara kebenaran teologis dan narasi palsu telah melemahkan daya kesaksian gereja. Tujuan penelitian ini adalah merumuskan strategi teologis dan praktis bagi gereja dalam mengkomunikasikan Amanat Agung secara otentik di tengah krisis kebenaran. Menggunakan metode kualitatif deskriptif dengan pendekatan studi pustaka, maka dapat disimpulkan bahwa peran pemahaman akan hakikat Amanat Agung dalam teologis dan juga pengetahuan akan Krisis di era post-truth dan tantangan gereja dalam mewartakan kebenaran. Diharapkan tidak menghalangi untuk mengaktualisasikan mandat Amanat Agung sebagai mandat pewartaan kebenaran di tengah krisis post-truth dan juga adanya strategi gereja menghadapi disinformasi dalam misi pewartaan dalam dunia yang gelap oleh disinformasi.